ASPiH standards for simulation-based education: process of consultation, design and implementation. (November 2018) - Purva, Makani; Nicklin, Jane
Abstract : There is widespread enthusiasm and emerging evidence of the efficacy of simulation-based education (SBE) but the full potential of SBE has not been explored. The Association for Simulated Practice in Healthcare (ASPiH) is a not-for-profit membership association with members from healthcare, education and patient safety background. ASPiH's National Simulation Development Project in 2012 identified the lack of standardisation in the approach to SBE with failure to adopt best practice in design and delivery of SBE programmes. ASPiH created a standards project team in 2015 to address this need. The article describes the iterative process modelled on implementation science framework, spread over six stages and 2 years that resulted in the creation of the standards. The consultation process supported by Health Education England resulted in a unique document that was driven by front line providers while also having strong foundations in evidence base. The final ASPiH document consisting of 21 standards for SBE has been extensively mapped to regulatory and professional bodies in the UK and abroad ensuring that the document is relevant to a wide healthcare audience. Underpinning the standards is a detailed guidance document that summarises the key literature evidence to support the standard statements. It is envisaged the standards will be widely used by the simulation community for quality assurance and improving the standard of SBE delivered.